Effectiveness of educational intervention on knowledge and attitude of adolescent sexual reproductive health among adolescents in selected public school, Jhapa. - Kathet, Alisha Pokhrel (2021)
ABSTRACT: Introduction: Sexual and reproductive health covers all aspects of adolescent health. Rapid development of knowledge and attitude take place during adolescent period carries many positive aspects as well as potential negative consequences especially in area of sexual and reproductive health which can have lifelong effects on individual, family and society. Proper education in this age group is important to enable them to prevent themselves from different sexual and reproductive health problem. Objective of this study was to find out effectiveness of educational intervention on knowledge and attitude regarding sexual and reproductive health among adolescents of selected public school, Jhapa. Method: A quasi experimental study with pretest- posttest design was carried out in two randomly selected schools with similar settings in Jhapa, Nepal. All the subjects were divided into two groups: experimental and control, each comprised 70 students. Structured self-administered questionnaires, likert scale and educational intervention package consisting of information on sexual and reproductive health were used as a tool of investigation. Pretest were taken in both group. Educational intervention was implemented in experimental group and after 15 days post-test was carried out in both groups. Paired t-test and independent t-test were used for data analysis and p value < 0.05 was considered as significance. Result: The mean (+-sd) pretest score of the experimental group on knowledge of sexual and reproductive health was (45.14 +-8.90) and of the control group was (43.18+-7.84) (p value:0.17). After educational intervention changes in mean score of knowledge and attitude were observed. In experimental group (94.67 +- 1.91) was statistically significant (p value: <0.001) whereas no significant change was seen in control group (43.86+-7.84). Similarly, post-test scores of attitude towards sexual and reproductive health were favorable in the experimental group than in the control group (p<0.001). Conclusion: This study found that effectiveness of educational intervention in improving knowledge and attitude of sexual and reproductive health. Thus, it can be recommended that school teachers and school health nurse should be counseled to take interactive sessions encouraging students to clear their queries freely.